2014
DOI: 10.1080/09687599.2014.910108
|View full text |Cite
|
Sign up to set email alerts
|

Recognising the agency of people with dementia

Abstract: People with dementia have been assumed to possess weak or even no agency, so this paper provides a novel contribution to academic debate by examining their actual potential for agency. The author draws on findings from a qualitative study of everyday decision-making by people with dementia that aimed to identify the role of social factors (such as gender) in influencing their involvement in decisions. Whilst decision-making constitutes a form of deliberative agency, the research also identified when agency was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(118 citation statements)
references
References 58 publications
4
105
0
9
Order By: Relevance
“…This is consistent with the literature that reports that PwD maintain a significant level of social agency [45]. The study by Boyle [46] highlights that "people with dementia who lack deliberative capacity can nonetheless demonstrate creative capacity for agency," which is part of the sociologic construct of personhood. The staffs' self-reported actions are compassionate and consistent with their beliefs.…”
Section: Discussionsupporting
confidence: 78%
“…This is consistent with the literature that reports that PwD maintain a significant level of social agency [45]. The study by Boyle [46] highlights that "people with dementia who lack deliberative capacity can nonetheless demonstrate creative capacity for agency," which is part of the sociologic construct of personhood. The staffs' self-reported actions are compassionate and consistent with their beliefs.…”
Section: Discussionsupporting
confidence: 78%
“…Throughout the analysis of the emergence and development of the care-collectives, we explored the links between care-relations, citizenship and knowledge, paying attention to what the care-collectives accomplished. Whilst most citizenship studies conceive of agency and citizenship as individual capacities (Boyle, 2014;Kontos, 2003), we have demonstrated that agency and citizenship might instead be understood as collective achievements demanding continuous enactment and re-enactment. We found that care-collectives are socio-material networks of relations that might facilitate the achievement of agency and citizenship.…”
Section: Discussionmentioning
confidence: 99%
“…Bartlett and O'Connor emphasize growth, social position, purpose, participation, community, and freedom from discrimination. Others recognize agency as embodied consciousness (Kontos, 2003), or as alternatively habituated, embodied, or emotional (Boyle, 2014). Yet another body of literature shows that the practice of citizenship is situational, depending on other people (Österholm & Hydén, 2014), places, and materialities (Pols, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…«Agency» handler om evnen til å uttrykke seg, enten gjennom verbale uttrykk eller kroppsspråk, og knyttes ofte til egenskaper ved individet. For personer med demens kan «agency» vaere kroppslig og habituelt forankret (Boyle, 2013(Boyle, , 2014Kontos, Grigorovich, Kontos og Miller, 2016). Anerkjennelse (recognition) handler om at mennesker har en iboende verdi som må respekteres for at medborgerskap skal bli realisert.…”
Section: Medborgerskap Praksiser Og Praxiografiunclassified